Registered Clinical Trials Comprising Pregnant Women in China: A Cross-Sectional Study - Zhao, Yi; Du, Guiping; Luan, Xiaofei; Yang, Hui; Zhang, Qiongguang; Zhang, Zhengfu; Wang, Subiao (Frontiers in Pharmacology, 2022)
Background: In this study, an investigation was conducted on clinical drug trials comprising pregnant women in China that provided data on the quantity, properties, source of funding, and geographical distribution regarding registration and post-marketing studies. Methods: We conducted a cross-sectional, descriptive study of clinical trials of pregnant women in China through December 30, 2021, and it was registered on the official Drug Clinical Trial Information Management Platform (ChiCTR) (http://www.chinadrugtrials.org.cn) established by the State Food and Drug Administration of China (Chinese FDA). Results: This study encompassed 72 registered trials (0.46%, 72/15539) were included for data analysis. Of these trials, 43.1% trials were started between 2013 and 2016, and nearly half of the trials (48.6%) were completed. Industries were listed as the primary sponsor for 95.8% trials. Economically developed eastern China and northern China, accounting for 69.5% of the 72 registered trials, were the most frequently identified study locations. Regarding study designs of these trials, more than half of the trials (70.8%) were randomized, 61.1% were a parallel assignment, 33.3% were phase 3, and half of the trials (54.2%) were open-label. In total of 23 trials met the requirements after excluding trials of cancer and/or of postmenopausal women, accounting for 0.15 % of the 15,539 registered trials in the ChiCTR websites. Of the 72 clinical trials, there include 54 drugs regarding 18 indications. Of these indications, the highest proportion of the trials is osteoporosis (27.8%), followed by cancer (22.2%), assisted reproduction (13.9%), and other indications (13.9%). Conclusion: This survey revealed a significant shortage in the development, evaluation and safety trials of pregnancy-related drugs in China. Modifying or adding legislation, and providing financial incentives may therefore encourage pharmaceutical companies to conduct additional clinical trials on pregnant women.